Penerapan Sistem Pakar Menggunakan Metode Nearest Neighbor Mendiagnosa Gangguan Kesehatan Pengguna Minuman Keras - Lince Tomoria Sianturi; Tegar Sabatia Tarigan (STMIK Budi Darma, 2019)
Expert systems in general are systems that try to adopt human knowledge to computers so that computers can solve problems as is usually done by experts. Or in other words an expert system is a system that is designed and implemented with the help of certain programming languages to be able to solve problems as done by experts. It is expected that with this system, lay people can solve certain problems, either 'a little' complicated or even complicated 'without' the help of experts in the field. As for experts, this system can be used as an experienced assistant. This system diagnoses the types of health problems of liquor users based on the symptoms entered into the system. This developed application aims to determine which liquor users consume by only paying attention to the criteria experienced by liquor users. Using the Nearest Neighbor Method is able to show a measure of certainty about a fact from the existing criteria. System output in the form of search results for liquor users is used by users based on symptoms.